Using the EU-SILC to model the impact of the economic crisis on inequality - Cathal O'Donoghue; Jason Loughrey; Karyn Morrissey (Institute for the Study of Labor (IZA), 2013)
In this paper we attempted to chart the impact of the early part of Ireland's economic crisis from 2008-2010 on the distribution of income. In order to decompose the impact of components of income, we utilised a microsimulation methodology the EU-SILC User Database. In order to do this we had to develop a simulation based methodology to disaggregate the main 6 benefit variables in the EU-SILC into 17 used in our tax-benefit model. Validating, our results were positive, giving us confidence in our methodology. We utilised the framework to model changes to the level of income inequality from the period just before the crisis in 2004 to after the crisis in 2010. In terms of the impact of the economic crisis, we found that the income inequality fell in the early part of the crisis, but rose steadily and then rapidly. Much of this change was due to rising inequality of market incomes, (even when discounting unemployment). This was due to the differential effect of the downturn on different sectors where some sectors such as the construction and public sectors were significantly hit, while the international traded sectors have been relatively immune from the downturn and have seen continued growth. The impact of the tax-benefit system has been to mitigate this upward pressure, with a gradual rise in the redistributive effect of the tax-benefit system driven by an increase in demand on the benefits side and increased progressivity on the tax side.
Keywords: I38; C53; 330; inequality; microsimulation; macro-economic change